A cross‐sectional survey of patients with open surgical wounds in Slovenia. (13th December 2018) - Pađen, Ljubiša; Griffiths, Jane; Cullum, Nicky
Abstract: Most surgical wounds heal by primary intention, that is, the wound is closed with sutures, clips, or glue. However, some surgical wounds are either left open to heal from the bottom up ("healing by secondary intention") or break open partially or fully after primary closure. There is little basic knowledge about the occurrence and natural history of surgical wounds healing by secondary intention (SWHSI); therefore, the aim of this survey was to estimate the number of people with SWHSI in Slovenia, the nature of these wounds, and to investigate how they are managed. A multiservice, cross‐sectional survey was carried out over a 2‐week period in the city of Ljubljana, Slovenia (population 288, 919). Healthcare professionals across health and social care settings completed one anonymised form for each patient with a SWHSI. Forms were completed for 110 patients. The point prevalence of SWHSI was 0.38 per 1, 000 of the population (95% CI: 0.33–0.44). Patients' mean age was 50.5 years. The majority of SWHSI were planned to heal by secondary intention before surgery (76/110, 69%). Of SWHSI, 83% (92/110) were treated with wound dressings, and 6% were treated with negative pressure wound therapy. Data were missing for 11 cases. This survey is the first to provide essential information about the extent, nature, and treatment of SWHSI in Slovenia. Furthermore, it is one of the latest of a very small number of studies to have contributed to knowledge about SWHSI globally. The results from the survey can be used for planning future research, health resources management, and policy development.